Experimental investigation on system performance using palm oil as hydraulic fluid - Wan Nik, W.B.; Maleque, Md. Abdul; Ani, F. N.; Masjuki, H.H. (Emerald Group Publishing Limited, 2007)
Purpose – The aim of this paper is to investigate hydraulic system performance using vegetable-based palm oil as hydraulic fluid. Design/methodology/approach – The hydraulic system performance test at different operating conditions, such as pressure, speed and oil ageing, was performed using a Yuken vane pump test rig. The endurance system performance test was also conducted for 200 and 400 h. The effect of speed on flow slip coefficient in discrete and continuous tests was studied. In discrete testing, pressure of 35 and 200 bar and speed of 750 and 1,439 rpm were used in determining flow slip coefficient. The instantaneous data were recorded in a computer using an analog-to-digital data acquisition system with respect to time and the parameters stored were reservoir temperature, return line temperature, suction and delivery pressures, instantaneous flow rate, total flow, total running time and torque. The obtained results were interpolated for future prediction of the system performance. Findings – The experimental and interpolated results showed that slip coefficient decreases with increasing pump speed. The effect of aging condition on volumetric efficiency showed that the efficiency increases with aging period due to increase in oil viscosity. Practical implications – This vegetable-based palm oil could be a potentially useful substitute for mineral-based energy transport media such as hydraulic fluid. Originality/value – The investigation of hydraulic system performance using palm oil as hydraulic fluid is scarce in the literature. Therefore, the current study is quite new for the hydraulic system performance and it is hoped that it will provide a high value to researchers for further research before it can be used as hydraulic fluid. Keywords Oils, Vegetable fats, Hydraulic engineering, Pumps